Penguatan Pola Asuh Demokratis di TK Pertiwi 34 Patemon - Amelindha, Nabilla Fasya; Noor, Zaima Aulia; Adiningrum, Aisha Inastya; Septiana, Laily Wakhidah; Rohmah, Naili; S, Sugiana (Yayasan Daarul Huda Kruengmane, 2025)
Parenting is very important for children because it determines how the child's journey and destiny will be in the future so that all behavior, actions, values, morals, rules, and beliefs held by children are influenced by the role of parents in educating. However, this is different in the real world, many parents are not aware of their role as figures who are dependent on children so that they become anarchic, destructive figures, and carry out other negative behaviors. The problem of parenting also occurs in Pertiwi 34 Patemon Kindergarten where many parents lack knowledge related to parenting so that many parents unknowingly apply parenting patterns that are not good for child development. Community service is carried out in the form of Socialization through Power Point media. The presentation of material on